Perancangan Sistem Informasi Penjualan Snack Bouquet Menggunakan Metode Rad Berbasis Web Pada Narch Bouquet - Nandi adi nugroho; Khautsar Rizaldi achmad (PT Jurnal Cendekia Indonesia, 2025)
Narch Bouquet's manual business processes, such as sales recording, stock management, and ordering, occurred without an integrated system, resulting in inefficiencies and data errors. To address these issues, a web-based sales information system was designed using the Rapid Application Development (RAD) method. The RAD method was chosen because of its ability to accelerate the development process by directly involving users in each prototyping iteration. Sales reporting, stock management, ordering, and product catalog features are all part of the developed system. This system can run in real-time and responsively using web technologies such as HTML, CSS, JavaScript, and Node.js. Testing results show that each system feature can meet user needs and improve customer experience and business management. This system is expected to be further developed flexibly to support future business growth using the Rapid Application Development (RAD) approach.